The Digital Sanctuary: Forging Legal And Ethical Frameworks For Interfaith Coexistence Online - Utari, Indah Sri; Ramada, Diandra Preludio; Kamal, Ubaidillah; Damayanti, Ratih; Alias , Nizamuddin (Universitas Negeri Semarang, 2025)
The internet has profoundly transformed interfaith relations, offering an unprecedented global arena for dialogue and community building. Yet this transformative power is shadowed by a growing threat: the digital space is increasingly weaponized as a battleground for religious tensions, fueled by hate speech, misinformation, and targeted harassment. The absence of robust legal and ethical frameworks tailored to the complexities of online interaction leaves interfaith communities vulnerable and undermines genuine cooperation. This article introduces the conceptual model of a “digital sanctuary”—a deliberately designed and protected online space where diverse faiths can coexist and flourish. Achieving this ideal is not an organic outcome of technology but requires intentional, multi-faceted efforts from all stakeholders. The paper critically examines regulatory gaps and ethical dilemmas obstructing interfaith harmony online, highlighting the limitations of fragmented national laws in a borderless environment and analyzing the responsibilities of technology platforms. We advocate moving beyond simple content moderation toward a proactive, rights-based approach that prioritizes the safety and dignity of religious minorities. By proposing a model of “digital jurisprudence,” the article calls for holistic guidelines that extend beyond traditional statutes. These include policy recommendations for algorithmic transparency, community-led dialogue, and greater international cooperation to establish standards that balance freedom of expression with protection from religious incitement. Ultimately, the paper contends that the future of peaceful interfaith coexistence depends on transforming the digital realm from a passive, ungoverned space into a resilient ecosystem where principles of mutual respect are systematically protected and nurtured